Prevalencia de hipertensión arterial en los empleados de Suramericana de Seguros Medellín: 1996 (1997)
ABSTRACT: High blood pressure as well as cardio-vascular, renal, and brain-vascular diseases related to it are within the ten first causes of morbi-mortality in Medellín City-Colombia. The study aims at identifying high blood pressure individuals in the Insurance Company Suramericana with headquarters in Medellín-Colombia, in order to prevent complications and to give education to modify risk factors. A survey was applied to 193 employees. This survey included modifying and non-modifying risk factors mostly related to the génesis of high blood pressure. Findings show that the prevalence of high blood pressure in the simple was 13,02%. No significant relation between the smoking tobacco habit and the intake of alcohol with high blood pressure was found. Likewise, it was found that 56% of individuals with high blood pressure showed family history with the same problem, and that 44% of the individuals did not practice any sports. Finally, some recommendations are given in order to reduce the increase of the prevalence of high blood pressure in this company.